Self-reported sensory descriptors are associated with quantitative sensory testing parameters in patients with cervical radiculopathy, but not in patients with fibromyalgia - Tampin, Brigitte; Briffa, Kathy; Slater, Helen (John Wiley & Sons Ltd., 2012)
Background: The painDETECT questionnaire (PD-Q) has been used as a tool to characterize sensory abnormalities in patients with persistent pain. This study investigated whether the self-reported sensory descriptors of patients with painful cervical radiculopathy (CxRAD) and patients with fibromyalgia (FM), as characterized by responses to verbal sensory descriptors from PD-Q (sensitivity to light touch, cold, heat, slight pressure, feeling of numbness in the main area of pain), were associated with the corresponding sensory parameters as demonstrated by quantitative sensory testing (QST). Methods: Twenty-three patients with CxRAD (eight women, 46.3 ± 9.6 years) and 22 patients with FM (20 women, 46.1 ± 11.5 years) completed the PD-Q. Standardized QST of dynamic mechanical allodynia, cold and heat pain thresholds, pressure pain thresholds, mechanical and vibration detection thresholds, was recorded from the maximal pain area. Comparative QST data from 31 age-matched healthy controls (HCs; 15 women) were obtained. Results: Patients with CxRAD demonstrated a match between their self-reported descriptors and QST parameters for all sensory parameters except for sensitivity to light touch, and these matches were statistically significant compared with HC data (p ≤ 0.006). The FM group demonstrated discrepancies between the PD-Q and QST sensory phenotypes for all sensory descriptors, indicating that the self-reported sensory descriptors did not consistently match the QST parameters (p = ≤0.017). Conclusion: Clinicians and researchers should be cautious about relying on PD-Q as a stand-alone screening tool to determine sensory abnormalities in patients with FM.